Poems from Into the Night that Flies So Fast - MILENA WILLIAMSON (Estudios Irlandeses, 2023)
These poems form part of a sequence on the life of Bridget Cleary (1867-1895). Cleary was killed by her husband, who claimed at trial to be acting under the belief that his wife had been abducted by fairies and replaced with a changeling. A conversation with Joe Lines establishes the poems’ context and development.